2019
DOI: 10.1002/cche.10183
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes associated with electron beam irradiation of rice and links to kernel discoloration during storage

Abstract: Background and objectives: Rice kernel discoloration during storage results in significant economic losses to rice growers and processors. This study aimed to elucidate the extent of chemical changes and microbial involvement on discoloration of rice kernels during storage. To segregate and/or diminish the effects of microbes, one lot of hybrid long-grain rice (XL753) samples was irradiated with nonthermal electron beam (EB) dose of 14 kGy. The irradiated and nonirradiated control samples of rice at a moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The control sample had an initial mold load of 5.74 log CFU/g. Mohammadi Shad, Steen, Devlieghere, Mauromoustakos, and Atungulu () and Oh et al () found the total mold load on freshly harvested rough rice to be above 5 log CFU/g. Figures 3a and 4a show the effects of IR treatment using broadband and selected wavelengths on mold load, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The control sample had an initial mold load of 5.74 log CFU/g. Mohammadi Shad, Steen, Devlieghere, Mauromoustakos, and Atungulu () and Oh et al () found the total mold load on freshly harvested rough rice to be above 5 log CFU/g. Figures 3a and 4a show the effects of IR treatment using broadband and selected wavelengths on mold load, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Several techniques have been applied to decontaminate cereal and other crops from fungi and mycotoxins. For example, electron beam irradiation was able to significantly reduce the fungal load on rice samples (Mohammadi Shad et al., 2019c). Also, utilization of IR heating demonstrated to deactivate fungi on grains by thermal denaturation of proteins and nucleic acids in microorganisms (Pan & Atungulu, 2010; Ramaswamy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…suitable for storage (US Grains Council, 2019) to prevent fungal proliferation and mycotoxin accumulation. When ingested, contaminated corn poses significant health hazards to humans and animals (Mohammadi Shad, Ghavami, & Atungulu, 2019a, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…However, this system has several drawbacks, such as longer drying durations, dependency on weather, and nonuniform drying patterns. Longer durations and incomplete drying subject the corn to prolonged storage at high MC, leading to reduced corn quality (Magan & Aldred, 2007; Mohammadi Shad, Ghavami, & Atungulu, 2019; Mohammadi Shad, Steen, Devlieghere, Mauromoustakos, & Atungulu, 2019). Also, convective heating used for the rapid drying of corn causes corn discoloration and kernel shrinkage, and does not adequately deactivate fungi (Wilson, Atungulu, & Olatunde, 2017).…”
Section: Introductionmentioning
confidence: 99%